2015
DOI: 10.1002/jsfa.7271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applying molasses, lactic acid bacteria and propionic acid on fermentation quality, aerobic stability and in vitro gas production of total mixed ration silage prepared with oat–common vetch intercrop on the Tibetan Plateau

Abstract: Our findings show that TMR prepared with oat-common vetch intercrop can be well preserved. Although propionic acid is compatible with lactic acid bacteria, and when used together, they had minor effects on fermentation, aerobic stability and in vitro digestibility of TMR silage prepared with oat-common vetch intercrop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 37 publications
8
53
3
3
Order By: Relevance
“…The aerobic stability with LP treatment decreased as corn ratio increased in forages mixture (Table 4) and an increase in alfalfa ratio may explain this result due to a higher content of AA produced in alfalfa-corn mixed silage with more alfalfa, whereas two studies indicated that the high aerobic stability of alfalfa silage could be attributed to certain antimicrobial substances produced over the course of fermentation O'Kiely and Muck 1992) and these substances produced during fermentation are possibly apt to enhanced the stability of mixed silage with a higher proportion of alfalfa. For 60 and 80% corn silages, the aerobic stability and pH value with AD and PD treatments was higher and lower, respectively, in comparison with LP after 7 days of exposure to air, which is agreement with Kleinschmit et al (2005) and Chen et al (2016). The antimicrobial properties of these additives result from their ability to pass across the cell membrane in the undissociated form and release hydrion in the cytoplasm.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The aerobic stability with LP treatment decreased as corn ratio increased in forages mixture (Table 4) and an increase in alfalfa ratio may explain this result due to a higher content of AA produced in alfalfa-corn mixed silage with more alfalfa, whereas two studies indicated that the high aerobic stability of alfalfa silage could be attributed to certain antimicrobial substances produced over the course of fermentation O'Kiely and Muck 1992) and these substances produced during fermentation are possibly apt to enhanced the stability of mixed silage with a higher proportion of alfalfa. For 60 and 80% corn silages, the aerobic stability and pH value with AD and PD treatments was higher and lower, respectively, in comparison with LP after 7 days of exposure to air, which is agreement with Kleinschmit et al (2005) and Chen et al (2016). The antimicrobial properties of these additives result from their ability to pass across the cell membrane in the undissociated form and release hydrion in the cytoplasm.…”
Section: Discussionsupporting
confidence: 74%
“…Alfalfa silage remained stable for more than a week after exposure to air , whereas corn silage exposed to air spoils easily (Nishino 2011). The aerobic stability of alfalfa-corn mixed silage perhaps decreases with a higher ratio of corn and propionic acid (PA) and propionate have been used to enhance the aerobic stability of silage (Kleinschmit et al 2005;Chen et al 2016). So far there is little information simultaneously concerning the quality and aerobic stability of alfalfa-corn mixed silage.…”
Section: Introductionmentioning
confidence: 99%
“…The dried fresh material and silage samples were analyzed for DM (method 934.01), CP (method 984.13), ash (method 942.05) and EE (method 920.39) with the method of AOAC . The WSC were determined using the method of Chen et al . NDFom (with heat‐stable α‐amylase), ADFom and acid detergent lignin (ADL) analysis were subsequently performed following the procedure of Van Soest et al .…”
Section: Methodsmentioning
confidence: 99%
“…The second subsample was preserved as a wet sample at −20 °C. A 35 g wet sample was extracted in 70 mL of deionized water at 4 °C for 24 h to obtain the cold extract, which was used to analyze silage fermentation end‐products as described by Chen et al . The pH of the water extract was measured with an electrode pH meter (HANNA pH 211, Hanna Instruments, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…The challenge would be to make ensiling of grass feasible by increasing the growth rates of lactic acid bacteria, dropping silage pH, and enhancing fermentation (Keady and Kiely, 1998;McDonald and Henderson, 1962;Nishino et al, 2012;Chen et al, 2016). If possible, this would configure alternative usage of a potentially pollutant byproduct from biofuel production.…”
Section: Introductionmentioning
confidence: 99%